Implementation of Multicultural Education in an Effort to Develop Santri's Tasamuh Attitude in Islamic Boarding Schools in Lampung Tengah Regency - Cecep Safrudin; Citra Ayu Anggraini (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Pesantren is very open to education, culture and traditions that develop in the community, which has similarities with multicultural values that prioritize respect for different cultures and cultures. This is confirmed by the diversity of different santri backgrounds in the pesantren community. Researchers found that boarding schools in Central Lampung Regency have santri consisting of various ethnic groups, such as Javanese, Sundanese, Lampung, Padang, and Palembang. This reality can cause problems if the education process is carried out in a discriminatory manner against one particular tribe. The purpose of this research is to find out the materials and methods of education as well as the implementation of multicultural education in an effort to develop the attitude of tasamuh santri in boarding schools in Central Lampung Regency. This research is a qualitative field research conducted in Islamic boarding schools in Central Lampung related to multicultural education in Islamic boarding schools in which there are various complex and dynamic problems, such as interactions between students and residents of Islamic boarding schools who are different in terms of ethnicity and culture. Researchers in collecting the necessary data as a source of information, using observation, interview and documentation techniques. From the data obtained, then collected and processed in order to draw a conclusion. Based on the results of the study, it can be concluded that multicultural education in Walisongo, Roudhotusholihin, and Al-Hidayah Islamic Boarding Schools is carried out in the form of placing students with different ethnic, cultural, and economic backgrounds in the same dormitory. This condition allows santri to understand cultural and language differences, and encourages a sense of togetherness and acceptance of other santri. Multicultural-based learning materials at Walisongo, Roudhotusholihin and Al-Hidayah Islamic Boarding Schools can be seen from the material about ahlussunnah wal jama'ah (Aswaja), which prioritizes the attitude of tawasuth (moderate), i`tidal (proportional), tasamuh (tolerant), and tawazun (balanced). Social interactions at Walisongo, Roudhotusholihin and Al-Hidayah Islamic Boarding Schools illustrate a plural community, which is based on akhlakul karimah values.